(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This paper investigates how artificial intelligence (AI) is transforming the translation industry, stressing both moral issues and progress. Although AI-driven tools have accelerated translation’s speed and efficiency, accuracy—especially with complex or culturally sensitive materials—raises questions. The conversation covers the possibility for misunderstandings, the difficulty of cultural sensitivity, prejudices in AI translating systems, and the effects for human translators. It also explores problems of accountability and the wider consequences of artificial intelligence translation for world communication. The paper underlines the need of ethical issues, continuous communication, and teamwork to guarantee that artificial intelligence in translation respects cultural diversity, advances equity, and preserves the value of human experience.